Analysis Of Protein Levels With Giving Kelor Leaf Extract (Moringa Oleifera) On Soy Milk - Fajar Nur Atmaja (Journal for Quality in Public Health, 2020)
Soy milk is a beverage product that is currently being favored by the people of Indonesia, to increase the protein content in soy milk needs to be substituted for other ingredients using Moringa Oleifera leaf extract. The purpose of this study was to analyze the organoleptic acceptability of soy milk by giving Moringa Oleifera leaf extract. This research is quantitative research with experimental research design using the True Experiment research method. This research was conducted in December 2018 until February 2019 at the Food Quality and Safety Testing Laboratory of the Agricultural Product Technology Department of the Faculty of Agriculture, University of Brawijaya Malang to test the protein content while the Organoleptic Test was carried out at STIKeS Satria Bhakti Nganjuk. The sample size is 20 panelists. The independent variable in this study was Moringa leaf extract while the protein content of soy milk. Data was collected using an organoleptic sensory test assessment table and a protein content test sheet using the Kjeldahl method. Data were analyzed using ANNOVA test with the results of H0 rejected and H1 accepted with a significant value <0.05 The results of ANOVA analysis get F count value of 105,405 and F table for testing 20 samples to get F table 4.35. So that it can be concluded that the addition of Moringa leaf extract 0% to 10% Significant and simultaneous organoleptic. Addition of Moringa Oleifera leaf extract to soy milk affected organoleptic acceptability and increased protein content of soy milk in accordance with the percentage of Moringa leaf extract levels added.